IMPROVING MATHEMATICS LEARNING OUTCOMES THROUGH THE IMPLEMENTATION OF PROBLEM-BASED LEARNING APPROACH IN ELEMENTARY SCHOOL PEKANBARU - Fajar Hamzah (Mathematics Research and Education Journal, 2024)
Students' low interest in learning creates challenges in the learning process, where a lack of motivation reduces students' active participation in teaching and learning activities. Therefore, it is essential to identify strategies that can increase students' interest in learning so that they are enthusiastic about participating in learning. This research aims to overcome the low learning outcomes of the Theme 1 Subtheme "My Daily Tasks at School" by applying the Problem-Based Learning model in class II at SDN 147 Pekanbaru. The research method used is Classroom Action Research with four main stages: planning, action implementation, observation, and reflection, carried out in 2 cycles, each consisting of 2 meetings. Data collection techniques include observation, tests, documentation, and quantitative and qualitative data processing. The research results show that applying the PBL model has improved student learning outcomes. In the pre-cycle, only eight students, or 31%, achieved completeness, then this increased to 18 students, or the equivalent of 69% in cycle I, and in cycle II, it reached 26 students or 100% completion.